2001
DOI: 10.1016/s0002-9440(10)64064-3
|View full text |Cite
|
Sign up to set email alerts
|

Augmented Senile Plaque Load in Aged Female β-Amyloid Precursor Protein-Transgenic Mice

Abstract: Transgenic mice (Tg2576) overexpressing human beta-amyloid precursor protein with the Swedish mutation (APP695SWE) develop Alzheimer's disease-like amyloid beta protein (Abeta) deposits by 8 to 10 months of age. These mice show elevated levels of Abeta40 and Abeta42, as well as an age-related increase in diffuse and compact senile plaques in the brain. Senile plaque load was quantitated in the hippocampus and neocortex of 8- to 19-month-old male and female Tg2576 mice. In all mice, plaque burden increased mark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
154
2
1

Year Published

2002
2002
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 258 publications
(178 citation statements)
references
References 30 publications
21
154
2
1
Order By: Relevance
“…Consistently, the plaque load in Tg2576 mice showed the same intersexual disparity (31). Although causes for this are unknown, our studies suggest that female-restricted increases of synaptic vesicle zinc may play a crucial role in the sexually disparate accumulation of amyloid plaques in Tg2576 mice.…”
Section: Discussionsupporting
confidence: 77%
“…Consistently, the plaque load in Tg2576 mice showed the same intersexual disparity (31). Although causes for this are unknown, our studies suggest that female-restricted increases of synaptic vesicle zinc may play a crucial role in the sexually disparate accumulation of amyloid plaques in Tg2576 mice.…”
Section: Discussionsupporting
confidence: 77%
“…This observation, previously noted by others in the Tg2576 line (APP sw ) (Callahan et al, 2001), points to the importance of gender in amyloid production/deposition and highlights the need to take this variable into account in the design of studies carried out on these mice, and possibly on other Tg mouse models of brain amyloidogenesis (Wang et al, 2003).…”
Section: Discussionsupporting
confidence: 56%
“…At 11 months of age, Tg2576 female mice were randomized to receive either a regular chow or chow supplemented with 2 IU/g diet vitamin E. The choice of using only female mice was based on previous work showing that in this animal model females exhibit a more consistent and greater amount of Ab formation and deposition than males (Callahan et al 2001). Preliminary experiments demonstrated that the selected dose of vitamin E significantly reduces in vivo LPO (Praticò et al 1998a).…”
Section: Animals and Surgical Proceduresmentioning
confidence: 99%